Distinct Expression of Coinhibitory Molecules on Alveolar T Cells in Patients With Rheumatoid Arthritis–Associated and Idiopathic Inflammatory Myopathy–Associated Interstitial Lung Disease. Issue 4 (15th February 2021) - Nakazawa, Maho; Suzuki, Katsuya; Takeshita, Masaru; Inamo, Jun; Kamata, Hirofumi; Ishii, Makoto; Oyamada, Yoshitaka; Oshima, Hisaji; Takeuchi, Tsutomu
Abstract : Objective: To identify immunologic factors in the lungs of patients with rheumatoid arthritis–associated interstitial lung disease (RA‐ILD) and patients with idiopathic inflammatory myopathy–associated ILD (IIM‐ILD) and to examine their pathologic mechanisms. Methods: Eleven patients with RA‐ILD, 16 with IIM‐ILD, 6 with drug‐induced ILD (DI‐ILD), and 8 healthy controls were enrolled. Peripheral blood (PB) and bronchoalveolar lavage (BAL) fluid were immunophenotyped by flow cytometry. Alveolar macrophages (AMs) were analyzed by coculture assay with PB naive CD4+ T cells from healthy individuals and RNA sequencing. Results: Several coinhibitory molecules were coexpressed on BAL fluid T cells (CTLA‐4, programmed death 1 [PD‐1], T cell immunoglobulin and mucin domain–containing protein 3 [TIM‐3], and lymphocyte activation gene 3 protein, from most to least), whereas only PD‐1 was expressed on PB T cells. CTLA‐4+PD‐1+CD4+ T cells were characteristic of RA‐ILD, whereas CTLA‐4+PD‐1+TIM‐3+CD8+ T cells were characteristic of IIM‐ILD. BAL fluid PD‐1+CD4+ T cells rarely expressed CXCR5, but their levels correlated with levels of plasmablasts and plasma cells (ρ = 0.57, P = 0.006), indicating that most of them would be considered peripheral helper T cells. In coculture experiments, AMs from patients with RA‐ILD and IIM‐ILD induced more PD‐1 and TIM‐3 on T cells ( P < 0.05), suggesting that coinhibitory molecule expression on BAL fluid T cells was partly due to AMs. RNA sequencing showed significant down‐regulation of PD ligand 1/2 genes in AMs from patients with RA‐ILD compared to those with DI‐ILD. Conclusion: We have identified differences in coinhibitory molecule expression between patients with RA‐ILD and those with IIM‐ILD. PD‐1 on T cells in RA‐ILD and TIM‐3 on CD8+ T cells in IIM‐ILD might be key factors in the disease process. Evaluation of coinhibitory molecules on BAL fluid T cells could be clinically useful.